Projeto de um servidor de vídeo sob demanda paralelo e distribuído - Lara, Carla Rodrigues Figueiredo (Universidade Federal de São Carlos, 2003)
This work presents an architecture for the development of a Video on Demand (Vod) Server using a Parallel Distributed File System. In the development of this work several aspects related to the project of VoD Servers are considered, including: optimized storing and retrieval of videos using appropriate striping unit and request sizes, and the monitoring of disk and network operation for the performance evaluation of the proposed system. The characteristics of the MPEG standard used for video compression are also studied and considered in the video transfers. We also discuss aspects related to the implementation of prefetching mechanisms in the VoD Server. The concept of cluster computing is also considered for efficient data distribution aiming at appropriate response time for satisfying the Quality of Service (QoS) require by the VoD users.
Keywords: Sistemas distribuídos; Servidor de vídeo; Vídeo sob demanda; Arquivos paralelos; MPEG; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO